Qadi Abd al-Jabbar on testimony, an epistemological approach - Abbas Dehqaninejad (پژوهشنامه فلسفه دین, 2016)
Epistemology of Testimony is one of the new branches of epistemology which seeks to cope with issues like the nature of testimony, its acceptability, and its relation to other sources of knowledge. This debate was also important for some Muslim theologians especially Qadi Abd al-Jabbar, who was one of the most important Mu’tazilite theologians. He believes that testimony is a way of reaching knowledge and responds to the doubts raised by some Islamic sects that reject testimony as a source of knowledge. He also believes -like Plantinga and some new philosophers in epistemology- that in transmission of knowledge, the main thing that transfers is the belief of the speaker and its properties. He also asserts that testimony is as reliable as other sources of knowledge and is not reducible to them. He has used his epistemic concepts about testimony as a foundation for proving some other religious beliefs such as occurrence of miracles.